The Endothelium in Acromegaly - Maffei, Pietro; Dassie, Francesca; Wennberg, Alexandra; Parolin, Matteo; Vettor, Roberto (Frontiers in Endocrinology, 2019)
Acromegaly is a rare disease with an increased morbidity and mortality predominantly due to cardiovascular diseases. In this review we examined the relationship between GH/IGF-1 excess and endothelium, from basic studies to clinical evidences. Many studies involving various arterial district (microvascular arteries of retina, kidney and brain, and major vessels as carotid and aorta) showed that GH/IGF-1 excess promotes endothelial dysfunction by several mechanisms. Increased endothelial proliferation, dysfunction of endothelial progenitor cells, increased oxidative stress and decreased oxidative defences are the main factors that are associated to endothelial dysfunction. In general population these alterations are associated to the development of atherosclerosis with an increased incidence of coronary artery and cerebral disease, but in acromegaly this is still a debated issue, despite the presence of many pro-atherogenic factors and comorbidities (hypertension, diabetes, sleep apnoea, metabolic syndrome). Preclinical markers of atherosclerosis such as arterial intima media thickness, pulse wave velocity and flow mediated dilation seems to be impaired in acromegaly. In addition, some studies analysed microcirculation in acromegaly reporting discordant results: in general population impairment of microcirculation is associated with an increased risk of cardiovascular disease so it would be important define its effective role in acromegaly. In conclusion, pathophysiology of endothelium dysfunction and the association to cardiovascular disease are not fully understood in acromegaly: further studies on this complex area are so necessary.